Pencak Silat Athlete Test Instruments and The Development of Sports Science - Bayu Iswana; Nasuka Nasuka; Sugiharto Sugiharto; Hadi Hadi (Universitas Negeri Semarang, 2023)
The instrument is one of the measuring instruments used as a data collection process in any form. In this literature study process that researchers want to know the role of science in the development of pencak silat sports through several test instruments produced from research results. The method used is to analyze the needs of the instrument so that it can complement the problems that occur and deficiencies in the sport of pencak silat silat . After carrying out a review of some of the literature analyzed that the resulting instrument consists of several tests that can complement the overall deficiencies that occur in the sport of pencak silat and the role of science in its development. The role of sports science looks very instrumental in order to meet the needs of pencak silat sports coaching, especially coaching in sports achievement. Some of the instruments produced utilize current technology using a research and development method approach.